Influence of packaging material on quality characteristics of minimally processed Mridula pomegranate (Punica granatum) arils during cold storage - BHATIA, KAVITA; ASREY, RAM; JHA, S K; SINGH, SURENDER; KANNAUJIA, PANKAJ KUMAR (The Indian Journal of Agricultural Sciences, 2026)
An experiment was conducted during 2011-2012 to observe the effect of packaging materials (Polypropylene, low density polyethylene and cryovac KPA bags) with different water and gas transmission rate on minimally processed Mridula pomegranate (Punica granatum) arils stored at 5 ± 2 ºC and 85 ± 5 % RH for 15 days. The quality of minimally processed arils was determined by measuring colour attributes (a* and b* value), physiological loss of weight (PLW),total soluble solids (TSS), aril firmness, respiration rate and total sugars at 3 day interval. The results indicated that packaging material influenced PLW, TSS, aril firmness, respiration rate and total sugars. Overall, arils packed in PP bags maintained better colour (a* and b* value) and aril firmness as compared to LDPE and KPA packed arils. Arils packed in PP showed a lower PLW, TSS and total sugars than samples packed in LDPE and KPA. Arils packed in PP bags also showed lowest mean respiration rate (44.73 ml CO2/kg/h) followed by arils packed in LDPE (50.19 ml CO2/kg/h),) and KPA (52.80 ml CO2/kg/h) at the end of storage. Among tested packaging materials, PP bags maintained better quality characteristics of minimally processed arils up to 15 days storage period.